DILEMA BARU PENDIDIKAN ISLAM PASCA OTONOMI DAERAH - Khabib Sharifudin; Miftahul Huda; Andre Arfiyanto; Mufasirul Bayani (CV. Adiba Aisha Amira, 2024)
The regional autonomy system means that most decisions and policies in a region can be decided by themselves in that region without any interference from the central government. The weakness of the decentralization system in regional autonomy is that the authority of the region can prioritize the interests of groups and groups and is used to gain personal or individual profits. This happens because it is difficult for the government at the central level to control. The purpose of writing this article is to find out: 1. The meaning of regional autonomy 2. To know the dilemma of Islamic education after autonomy and its impact on Islamic religious education 3. Problems in the Implementation of Educational Autonomy 4. Implementation of Regional Autonomy in the World of Education 5. Problems of Islamic Education 6. Repositioning Islamic Education in the Era of Regional Autonomy. This study used qualitative research methods. Meanwhile, data collection is done by observation, interviews and documentation. The data analysis uses data reduction techniques, data presentation and drawing conclusions.